Monitoring of the morbidity of measles in the Kharkiv region - Antusheva, Tetyana; Kalinichenko, Svitlana; Minukhin, Valeriy; Torianyk, Inna; Melentieva, Khrystyna; Moiseenko, Tetiana (Annals of Mechnikov’s Institute, 2022)
Introduction. Measles is a highly contagious disease that has a severe course in adults, immunosuppressed individuals, and newborns, and in pregnant women, it increases the risk of miscarriage, premature birth, and stillbirth. Many doctors still believe that measles affects only children. This leads to late diagnosis and spread of the pathogen. Another point complicating the diagnosis of measles infection is the formal attitude of society to vaccination against it. Cases of fatalities as a result of vaccinations contribute to the emergence of caution, a negative attitude towards the vaccination calendar, and acute mistrust of specialists. Refusals from vaccinations also contributed to the fact that low-quality drugs appeared on the market. The incidence of measles, despite the availability of effective preventive measures, remains an urgent medical and social problem worldwide, which is included in the list of infections that in the long term can be reduced to single cases. Infectious morbidity of the population to a certain extent depends on the quality of preventive measures, among which specific prophylaxis is the most successful, effective and cheapest medico-prophylactic means. Purpose: to monitor the incidence of bovine infection among the population of the Kharkiv region. Materials and methods. A retrospective analysis of the incidence of measles in the Kharkiv region for 2017-2020 was carried out with a study of vaccination history. Statistical data and reporting forms on epidemiological, virological and serological studies on bovine infection in the Kharkiv region for 2017-2020, presented by the State University "Kharkiv OLC of the Ministry of Health of Ukraine". People of both sexes, aged from 0 to 17 years, were examined. To predict the incidence and dynamics of the epidemic process, information about the actual protection of the vaccinated population from infection is necessary. According to the results of the study for the period 2017-2020, it was determined that in the Kharkiv region during 2018 - 2019 has only one vaccination. There was an increase in the proportion of the adult population among the sick, as well as the number of diseases with a severe course. The deterioration of the epidemic situation can be associated with the poor quality of vaccination, not excluding the facts of refusals and fictitious certificates (as evidenced by a fairly high percentage of diseases among vaccinated persons), as well as the migration of unvaccinated people in various hard-to-reach groups that transmit the infection to the general population. To the organization of mass vaccination in 2019-2020 it was possible to halt the further spread of infection, stabilize the epidemic situation and minimize its manifestations. The decline of the epidemic situation in 2020 was achieved due to the organization of mass vaccination among the population, especially children and in the centers of ethnic groups, which accounted for the largest percentage of diseases in the total number of registered cases. Conclusions. Thus, according to the results of the conducted research for the period 2017-2020, it was determined that in the Kharkiv region during 2018-2019 there was an increase in the incidence of cowpox infection primarily due to unvaccinated persons (including those with unknown vaccination status) and persons with incomplete vaccination, who has only one vaccination. There was an increase in the specific weight of the adult population among the sick, as well as the number of diseases with a severe course. The worsening of the epidemic situation can be associated with poor-quality vaccination, not excluding the facts of refusals and fictitious certificates (as evidenced by a fairly high percentage of diseases among vaccinated persons), as well as with the migration of unvaccinated people in various hard-to-reach groups that transmit the infection to the general population. Thanks to the organization of mass vaccination in 2019-2020, it was possible to stop the further spread of the infection, stabilize the epidemic situation and minimize its manifestations.